ON THE EXPERIMENTAL BICULTURE OF THE SEA BASS, LATES CALCARIFER (BLOCH) WITH OREOCHROMIS MOSSAMBICUS (PETERS) - Purushan, K S (Indian Journal of Fisheries, 2011)
has identified Sea bass (Lates calcarifer)culture as one of priority areas to developaquaculturc industry (Kungvankij, 1986). Inthe south cast Asian countries, commercialculture of L. calcarifer has received greatattention following the success achieved in itsartificial seed production (Brohmanoda, 1982;Maneewong, 1986; Awang, 1986)